Responses of water spinach (Ipomoea aquatica Forssk.) on growth, morphology, uptake rate and nutrients allocation under high ammonium concentration - Sutthathorn Chairuangsri (2018)
The effects of external NH 4 + concentration on growth, morphology, NH 4 + uptake and mineral allocation in Ipomoea aquatica were investigated under greenhouse conditions. Similar sized plants were grown on full strength Smart and Barko growth medium [1] with different levels of NH 4 + -N (0.5, 1, 5, 10 and 15 mM) for four weeks. Relative growth rate was high in plants fed with NH 4 + at concentrations of 0.5, 1 and 5 mM, but at higher concentrations the plants were stunted with few and short roots, old leaves were lost and growth of new ones was suppressed. Submerged stems and roots were damaged especially in plants supplied with 15 mM NH 4 + . The NH 4 + uptake rate tended to decrease with increasing NH 4 + supply. This may be due to damaged roots and stems which decreased efficiency of nutrient uptake. However, we found only small changes in mineral concentration in the tissue of both leaves and roots. We suggest that I. aquatica can be used for water treatment but the NH 4 + concentration must be less than 5 mM to prevent root and stem damage that cause minerals to be released from the plants and returned to the water treatment system.